Réponses

  • Utilisateur Brainly
2014-04-02T17:15:58+02:00
a) Développement:

A= (3x+1) (x+2) - 3(3x+1)
A= 3x² +6x +x +2 -9x -3
A= 3x² -2x -1

b) Factorisation:

A= (3x+1) (x+2) -3(3x+1) ⇒ On remarque le facteur commun
A= (3x+1) (x+2 -3) ⇒ On factorise par (3x1)
A= (3x+1) (x-1)

c) Résolution:

A= -1
3x² -2x -1 = -1
3x² -2x -1 + 1 = 0
3x² -2x = 0  ⇒ On factorise par x
x (3x-2) = 0

On applique la règle du produit nul:

x= 0  ou 3x -2 = 0
x= 0  ou    x= 2/3


d) Résolution:

A= 0
(3x+1) (x-1) = 0

On applique la règle du produit nul:

3x+1 = 0  ou   x-1 = 0
3x= -1      ou    x= 1
x= -1/3     ou    x= 1


Voilà ! J'espère t'avoir aidé(e) ! :)